(untitled) (diségno, 2019)
Military reasons, disputes over matters of borders, indications on the use of the land, appraisals for damage following natural disasters have led, over the last few centuries, to the production of a considerable archival graphic material, whose study allows us to understand the settlement geography of an area, grasping the architectural peculiarities of buildings and reconstructing their transformations, but also tracing signs of urban reality that have disappeared today, even before the traditional archaeological studies. No less important is the graphic study of these iconographic testimonies to understand the rules of representation known to the technicians of the time. Starting from the examination of archive folders, among the various papers numerous graphic documents have been traced which allowed to reconstruct the Lucanian settlement geography between the XVII and XIX centuries. A fundamental reflection was reser- ved to the graphic study of these maps which highlighted the knowledge of the time surveyors on the construction of the represented space, and how these were ‘adapted’ to the communication needs required by the different commissions.